Transcatheter Closure of a Paravalvular Leak Guided by Transesophageal Echocardiography and Three-Dimensional Printing - Xu, Chennian; Liu, Yang; Zhai, Mengen; Jin, Ping; Li, Lanlan; Ma, Yanyan; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background Closure of a percutaneous paravalvular leak (PVL) is a technically challenging procedure because of the specific anatomy postoperatively and the complex catheter techniques required. Transesophageal echocardiography (TEE) and three-dimensional (3D) printing might be helpful in identifying complex anatomical structures and the procedural design. Objectives The purpose of this study was to review our experiences with transcatheter closure of PVL guided by TEE and 3D (TEE&3D) printing. Methods A total of 166 patients with PVL after surgical valve replacement underwent transcatheter closure, from January 2015 through December 2020. Among these patients, 68 had preoperative guidance from TEE&3D printing. We reviewed the catheter techniques, perioperative characteristics, and prognosis. The median follow-up period was 36 (3–70) months. Results Acute procedural success was achieved in 154/166 (92.8%) patients; of these, 64/68 (94.1%) had TEE&3D guidance and 90/98 (91.8%) had transthoracic echocardiography (TTE) guidance. No hospital deaths occurred. All patients having percutaneous procedures were given local anesthesia, while 13 patients having transapical procedures were given general anesthesia. Multiple approaches were used, including transfemoral, transapical, and transseptal via the arteriovenous loop. We also deployed multiple devices, including the Amplatzer Vascular Plug II (AVP II), the Amplatzer duct occluder II, the patent ductus arteriosus (PDA) occluder, and the Amplatzer muscular ventricular septal defect occluder. Those cases guided by TEE&3D printing had shorter procedural times compared with those guided by TTE [(61.2 ± 23.4) vs. (105.7 ± 53.9) min, p < 0.05]. The fluoroscopic time was also shorter for operations guided by TEE&3D printing compared with those guided by TTE alone [(18.5 ± 11.4) vs. (27.3 ± 5.6) min, p < 0.05]. The complications included recurrent hemolysis, residual regurgitation, acute renal insufficiency, and anemia. There was no significant difference in the incidence of complications between the 2 groups. Conclusion Transesophageal echocardiography and 3D printing show advantages compared with standalone TTE in guiding the transcatheter closure of PVL with shorter procedural and fluoroscopic times. This minimally invasive treatment could provide reliable outcomes in selected patients. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT02917980].